Case Study Of Nasioncom - Imamudeen, Ashif (2006)
This research studies the situation of the communication infrastructure in Malaysia in terms of political, economical, social and technological factors. Nasioncom, being a developing player in the telecom sector, now had to find the way to fit in this new competitive environment as it is at a disadvantage of achieving competitive advantages compared to its rivals.